1988
DOI: 10.1021/ic00277a035
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine azide and fluorine nitrate: structure and bonding

Abstract: We report here predictions for the geometries of fluorine azide and fluorine nitrate and an analysis of their electronic structure based on ab initio calculations. Although the compounds were synthesized many years ago and some data exist on their reactivity,1-3 both are explosive and there has been much uncertainity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[34,35] The chemical formula of all Y 3 + complexes with non-macrocyclic ligands included in this study are shown in Scheme 2. The number of inner-sphere water molecules in some of the complexes wasa ssigned on the basis of available crystallographic data and solution studies performed on the Ln 3 + analogues ([Y(EGTA)(H 2 O)] À , [36,37] [Y(DTPA)(H 2 O)] 2À , [38] [Y(TTHA)] 3À [39] ). In other cases the complexesp resent variable hydration numbers in the solid state so the exact number of water molecules coordinated to Y 3 + cannot be predicted in as traightforwardm anner.F or instance, the sodium salt of [Y(EDTA)(H 2 O) 3 ] À wasf ound to contain three coordinated water molecules, while the structurally related[ Y(DCTA)(H 2 O) 2 ] À complex was reported to be bis-hydrated in the solid state.…”
Section: Structure Of the Y 3 + + Complexesmentioning
confidence: 99%
“…[34,35] The chemical formula of all Y 3 + complexes with non-macrocyclic ligands included in this study are shown in Scheme 2. The number of inner-sphere water molecules in some of the complexes wasa ssigned on the basis of available crystallographic data and solution studies performed on the Ln 3 + analogues ([Y(EGTA)(H 2 O)] À , [36,37] [Y(DTPA)(H 2 O)] 2À , [38] [Y(TTHA)] 3À [39] ). In other cases the complexesp resent variable hydration numbers in the solid state so the exact number of water molecules coordinated to Y 3 + cannot be predicted in as traightforwardm anner.F or instance, the sodium salt of [Y(EDTA)(H 2 O) 3 ] À wasf ound to contain three coordinated water molecules, while the structurally related[ Y(DCTA)(H 2 O) 2 ] À complex was reported to be bis-hydrated in the solid state.…”
Section: Structure Of the Y 3 + + Complexesmentioning
confidence: 99%
“…Since all four structures 7 គ -1 គ0 are much higher in energy than the transition states for dissociation of both the open and cyclic isomers, such rearrangements are extremely unlikely and were not pursued at higher levels of theory. 1 AЈ surface sampled by the vibrational wave function. It is important to distinguish two situations, one in which the state lives long enough ͑for example, microseconds͒ to be detected and the second in which the state lives long enough ͑for example, days͒ to be useful as an energetic species, with the latter situation requiring a more detailed analysis than the former.…”
Section: Rearrangements Between Isomers On the Singlet Potential Ementioning
confidence: 99%
“…The equilibrium structure of fluorine azide and its decomposition to N 2 (X 1 ⌺ g ϩ )ϩNF͑a 1 ⌬͒ have been studied in a number of experimental and theoretical works. [1][2][3][4][5][6] It was found that gas phase thermal dissociation of fluorine azide yields metastable NF͑a 1 ⌬͒ radicals, and the experimental activation barrier for this dissociation is 15 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability and its decomposition to N 2 have been studied in a number of experimental and theoretical works. [24][25][26][27] For the reaction HN 3 + N 3 F f N 6 + HF, according to the character of the reactants, the possible mechanism could be as follows: via the coulomb force, with no activation energy barrier Then, the H-F bond forms between the H atom of the HN 3 and the F atom of the N 3 F (see Figure 1). At the same time, the N-N bond also forms between the N1 and N2 atoms of the two reactants, leading to another molecule-molecule complex 2 via TS With the full cleavage of the H‚‚‚N bond in the complex 2, the complex 2 dissociates into two fragments N 6 and HF These calculations provide a theoretical suggestion for improved design of the corresponding HEDMs.…”
Section: Introductionmentioning
confidence: 99%